Расторжение индивидуальных трудовых договоров по инициативе работодателя - Сосна, Александр; Сосна, Борис (Tipografia "CentroGrafic" ,Cahul, 2016)
The authors consider the problem of submission of termination of the individual employment contract by the employer . Due to the fact that recently there has been the number of violations of labor rights of employees upon termination of individual employment contracts on the initiative of the employer, the authors examine the theoretical and practical aspects of the rules above.